Investigation of the three-dimensional hinge moment characteristics generated by the ONERA-M6 wing with an aileron - Zhang, G. Q. (2014)
The hinge moment characteristics for ONERA-M6 wing with aileron configuration have been investigated numerically based on the different gaps and deflecting angles. The results show that the effects on the wing made by the deflecting aileron are notable. Comparing with the nonaileron case, the chordwise pressure coefficient distribution for the wing with aileron has shown the totally different trends. The small gap can force the air flow through and form the extremely strong spraying flow. It can directly destroy the previously formed leading edge vortex (LEV). Due to the presence of the positive deflecting angle, the trailing edge vortex (TEV) will begin to generate at the trailing edge of the aileron. The induced secondary LEV will be mixed with the developing TEVs and form the stronger TEVs at the downstream position. Comparing with the subsonic flow, the curve for the supersonic flow has shown a good linear. The corresponding hinge moments are also extremely sensitive to the changing angle of attack, and the slope of curves is also bigger than that of the subsonic flow. The bigger gap and deflecting angle can result in the curve of hinge moment bending upward at high angle of attack. The corresponding pressure cloud and streamlines have also been obtained computationally and analyzed in detail.